Exposure to incivility hinders clinical performance in a simulated operative crisis. Issue 9 (31st May 2019) - Katz, Daniel; Blasius, Kimberly; Isaak, Robert; Lipps, Jonathan; Kushelev, Michael; Goldberg, Andrew; Fastman, Jarrett; Marsh, Benjamin; DeMaria, Samuel
Abstract : Background: Effective communication is critical for patient safety. One potential threat to communication in the operating room is incivility. Although examined in other industries, little has been done to examine how incivility impacts the ability to deliver safe care in a crisis. We therefore sought to determine how incivility influenced anaesthesiology resident performance during a standardised simulation scenario of occult haemorrhage. Methods: This is a multicentre, prospective, randomised control trial from three academic centres. Anaesthesiology residents were randomly assigned to either a normal or 'rude' environment and subjected to a validated simulated operating room crisis. Technical and non-technical performance domains including vigilance, diagnosis, communication and patient management were graded on survey with Likert scales by blinded raters and compared between groups. Results: 76 participants underwent randomisation with 67 encounters included for analysis (34 control, 33 intervention). Those exposed to incivility scored lower on every performance metric, including a binary measurement of overall performance with 91.2% (control) versus 63.6% (rude) obtaining a passing score (p=0.009). Binary logistic regression to predict this outcome was performed to assess impact of confounders. Only the presence of incivility reached statistical significance (OR 0.110, 95% CI 0.022 to 0.544, p=0.007). 65% of the rude group believed the surgical environment negatively impacted performance; however, self-reported performance assessment on a Likert scale was similar between groups (p=0.112). Conclusion: Although self-assessment scores were similar, incivility had a negative impact on performance. Multiple areas were impacted including vigilance, diagnosis, communication and patient management even though participants were not aware of these effects. It is imperative that these behaviours be eliminated from operating room culture and that interpersonal communication in high-stress environments be incorporated into medical training.